Current therapeutic strategies for HCV-associated cryoglobulinemia - F. Iannuzzella; G. Garini (PAGEPress Publications, 2011)
Cryoglobulinemia refers to the presence in serum of immunoglobulins, that reversibly precipitate at low temperatures. Cryoglobulins are classified according to their immunochemical properties as type I, composed of a single monoclonal immunoglobulin, and types II and III, referred as mixed cryoglobulinemia (MC), composed by a mixture of monoclonal (type II) and polyclonal (type III) IgM that have rheumatoid factor activity and bind to polyclonal IgGs. MC is a systemic vasculitis with cutaneous and multiple organ involvement including chronic hepatitis, membrano-proliferative glomerulonephritis, and peripheral neuropathy. In more than 90% of patients, MC is associated with chronic hepatitis C virus (HCV) infection, which is considered the triggering factor of the disease. Patients with HCV-related MC may be managed by means of etiological, pathogenetic or symptomatic therapeutic modalities. The choice of the more appropriate treatment is strictly related to the assessment of disease activity, and to the extent and severity of organ involvement. This paper reviews the currently available therapeutic strategies for MC syndrome, emphasizing the importance of HCV eradication, and the safety/efficacy of new biologic therapies for selective control of cryoglobulin-producing B-cells.